Corrosion process monitoring of reinforced concrete structure using fiber bragg grating (FBG) strain sensor / Omar Almubaied - Omar, Almubaied (2017)
Corrosion of steel reinforcement can occur without visible indication unless it creates cracks on concrete surface. In the context of structure safety, detecting cracks in a structure can be considered a late indication of the structural strength status. Additionally, steel reinforcement corrosion affects the behaviour of the structural member against load, where the vertical displacement of structural members such as beams can be changed. Therefore, measuring the deflection can improve the assessment of the structural health, which will increase the safety of the structure and reduce the repair cost if needed. In this study, an instrumentation for Fiber Bragg Grating (FBG) strain sensor was developed to monitor corrosion process and measure vertical displacement. Laboratory investigations were conducted to evaluate the proposed FBG mounting method that protects FBG during concrete casting and hardening to later facilitate effective detection of steel reinforcement corrosion as well as measurement of vertical displacements of reinforced concrete beams under loading. The mounting method was proposed based on the bend sensitivity of the FBG strain sensor, which enables the sensor to evaluate corrosion and vertical displacement without the need to compare with reference point. The laboratory investigations were divided into two phases. Phase 1 examined the capability of the FBG sensor to monitor steel corrosion process in concrete cylindrical specimens, while Phase 2 examined the capability of the FBG sensor to measure vertical displacement of reinforced concrete beam specimens under loading in addition to corrosion process monitoring. The impressed current technique was adopted to accelerate steel corrosion process during testing. In general, the measurement data provides a good correlation between the corrosion level and FBG wavelength shifts. On the other hand, in the measurement of vertical displacement in Phase 2, the mounting method was slightly modified to serve the purpose. The modified mounting method has demonstrated to be effective in allowing the FBG strain sensor to measure vertical displacement, from which a coefficient can be obtained from the correlation between the vertical displacement and FBG wavelength shifts. Finally, a statistical procedure for FBG sensing was introduced for assessing FBG measurements accuracy and interpretation.